The Successful Saga of a Cesarean Scar Ectopic with High βHCG Level - Rohatgi, Tanya B.; Buckshee, Kamal; Sahni, Reeti (Journal of Fetal Medicine, 2015)
Cesarean scar ectopic (CSE) is a rare life-threatening condition associated with hemorrhage, uterine rupture, disseminated intravascular coagulation or death during pregnancy. A rampant increase is worrisome. Early diagnosis is critical; awareness and high index of suspicion are essential. We report a 34-year-old woman with two previous cesarean sections, who was diagnosed to have an unruptured, viable CSE with high βHCG level (49,637. 08 mIU/mL). Local as well as systemic methotrexate failed initially. However, success was achieved when modified medical treatment was adopted.
Keywords: Cesarean scar; Ectopic pregnancy; Methotrexate